Unraveling the Transport and Fate of Polycyclic Aromatic Hydrocarbons Through Coupling Fluvial Geomorphic Modeling and Measured Data - Hosseiny, Hossein; Cao, Han; Smith, Virginia; Xu, Wenqing (Frontiers in Water, 2021)
Coastal zones receive upstream runoff and sediments, as well as the contaminants transported with sediments and flow. Constant urban growth in many coastal areas has raised an increasing concern about stream and floodplain contamination. This is a particularly challenging issue because fluvial hydraulics in the coastal zone is complex, due to the presence of backwater (BW) conditions which alter flow patterns and sediment transport regime. Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants that are widely distributed in urban areas and can be transported through stormwater runoff and by sediment facilitated transport. Even though this is a widespread problem in urban areas, the relationship between fluvial deposition and concentrations of PAHs is largely uninvestigated. To fill this gap, this paper investigates the correlation between PAHs concentration and sediment deposition in a backwater zone, using the lower Darby Creek, PA as a case study. A BW geomorphologic model was used to simulate the hydraulics of the flow in Darby Creek. The model identified locations of high and low shear stresses, erosion, and deposition of fluvial sediment. Twenty-eight core sediment samples, capturing a range of soil depths, were collected from the bed, the banks, and the floodplains of the creek and were analyzed for PAHs on a GC-MS. The results showed that PAHs concentrations were generally highest on depositional banks and were highly variable on the channel bed and in the floodplain. A comparative analysis was done to investigate the relationships between PAHs concentration in the soil, hydraulic regime, channel geometry, modeled shear stress, and soil depth. This analysis provides deeper insight into the transport and fate of PAHs in urban streams and floodplains, ultimately helping mitigate the impacts of pollutants on the environment.